Effects of severe acute respiratory syndrome coronavirus 2 (SARS-COV-2) Delta variant (B.1.617.2) on maternal and neonatal outcomes - Kalsang Dolma; Swati John; Rashmi Gulati (Journal of Global Health Reports)
# Background